Online education benefits instructors’ emotional labor management - Danielle Sonnenberg; Pamela Rutledge (Computers and Education Open, 2024)
The growth in online education preceded the pandemic, however, COVID-19 drastically altered the educational landscape by forcing the unprecedented shift of education from in-person to remote learning. This change heightened concerns over student outcomes due to a lack of emotional engagement that is critical to academic outcomes. To create a positive emotional connection in any learning environment, teachers must actively manage their emotions within professional guidelines. Studies on instructors’ emotional experiences are sparse, leading to a lack of understanding as to how instructors adapt their strategies and emotional labor in online versus in-person teaching modalities to build deep emotional connections with students. This study addresses this gap in the literature by asking instructors about their comparative experiences of emotional empathy and emotional labor in person and online. Nineteen qualitative interviews with higher education instructors experienced in both settings revealed three key findings: 1) creative use of empathy-building strategies online reduced instructors’ concerns over platform limitations, 2) the time lag in asynchronous online courses allowed instructors to more meaningfully address all student concerns and 3) contrary to expectations, emotional labor was experienced more intensely in face-to-face classes than online, suggesting that online settings gave instructors more space to manage emotional labor. This research centers on the debate between technological determinism and social constructionism: Are empathetic bonds and fulfilling professional experiences shaped by the teaching modality, or are they the result of adaptive pedagogies and strategies?